Playful participation with urban complexity. Evaluation of the co-located seriuos game Mobility Safari in Vienna. - Gugerell, Katharina; Jauschneg, Martina; Platzer, Mario; Berger, Martin (My University, 2017)
Die Frage der Einbeziehung der Bürger in die Stadtentwicklung und -planung hat in den letzten Jahren erheblich zugenommen. Traditionelle Planungs-, Steuerungs- und Kommunikationsansätze stoßen in einer komplexeren Stakeholder-Landschaft und einem zunehmenden Wunsch der Bürger nach Engagement an ihre Grenzen. Serious Games und Gaming werden zunehmend als Möglichkeiten für die erhöhte Einbindung von Stakeholdern und die Einbeziehung der Bürger in die Stadtplanung und Verwaltung betrachtet. Sie werden aber auch als Mittel zur Anregung von Lern- und Capacity Building-Prozessen und zur Sensibilisierung für urbane Kernthemen diskutiert. Der Artikel beleuchtet dieses Thema am Beispiel des Spiels "Mobility Safari", welches als Prototyp eines Serious Game für die Stadt Wien entwickelt wurde.

The issue of engaging citizens in urban development and planning has experienced a significant increase in recent years. Traditional planning, control and communication approaches are reaching their limits in a more complex stakeholder landscape and an increasing desire of citizens for engagement. Novel approaches to inform and involve citizens in a playful co-creation process are necessary. Serious games and gaming are increasingly considered as the magic bullet for elevated stakeholder involvement and citizen engagement in urban planning and governance. But they are also discussed as means to instigate learning and capacity building processes and to raise awareness for urban core topics. These learning processes can unfold in different formats, such as social or game-based learning. This paper investigates, if playing the serious game prototype "Mobility Safari" instigates social and specific learning processes and motivates players for a playful public participation. The Mobility Safari is a serious game prototype that was developed for the City of Vienna, integrating Vienna's smart city ambition to transition towards a more sustainable mobility system. The analysis illustrates that the serious game indeed instigates and evokes learning processes during the game play and in the debrief covering a broad range of different learning activities and social interaction. Incomplete rule-sets and un-governed situations triggered discussions where the players linked the game with their real-world experience and were urged to confront those experiences and actual practises. On the other hand, the willingness for active participation, which indeed takes a lot of effort, could be observed less often. Our analysis suggests that Mobility Safari is indeed a suitable mean for learning processes and support in a moderate way the interest in participation processes. We learned that a careful design, facilitation and sufficient time for a debrief to reflect on the game experience is crucial for a deeper learning experience that is meaningful for real-world contexts.
Keywords: Stadtentwicklungsplanung; Bewohnerbeteiligung; Partizipation; Kommunikation; Beteiligungsverfahren; Bürgerbeteiligung; Serious Game; Gaming